The evolving role of the superficial temporal vessels as anastomotic recipients in challenging microvascular reconstruction of the upper two-thirds of the face. Issue 9 (September 2022) - Mattine, Samuel; Payne, Karl Frederick Braekkan
Summary: Free-tissue transfer is now the standard of care in reconstructing head and neck defects. Microvascular reconstruction of the upper two-thirds of the face, particularly following recurrent malignant disease, however, remains a challenge. Retrospective review of all patients undergoing microsurgical reconstruction for defects of the upper two-thirds of the face between 2015 and 2019 revealed 17 free-tissue transfers where the superficial temporal vessels (STVs) were used as recipient vessels. Perioperative data, including return to theatre (RTT) and flap success rates were evaluated. Three patients required reoperation for vascular compromise. One of these patients ultimately lost the flap resulting in flap survival of 94%. This flap failure was, however, secondary to external factors distant to the flap and the anastomosis. In this patient, subsequent attempt at microvascular reconstruction was carried out successfully using contralateral neck vessels and vein grafts. We demonstrate the STVs are safe and reliable in microsurgical reconstruction for a variety of defects. Close proximity to the resection, reconstructing with flaps with a short pedicle, negating the need for neck access and/or high-risk anastomosis in a previously irradiated/operated vessel depleted neck are all highlighted indications. The pre-auricular/temporal access is familiar to the reconstructive surgeon and has excellent post-operative aesthetic results. We discuss key advantages of this approach and highlight potential complications and learning points – underlining the benefit of this approach for the head and neck reconstructive surgeon.